ANALYSIS THE EFFECT OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY AND SOCIAL CAPITAL ON FINANCIAL ICLUSION IN MALANG CITY - Rifianti, Anatalia; Mukhlis, Imam (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aims to determine the effect of financial literacy, financial technology and social capital on financial inclusion in the people of Malang City, East Java Province, Indonesia. This research is a research with a quantitative approach. This study uses primary data. The population in this study is the people of Malang City who use fintech products of the e-wallet type. The sampling technique used purposive sampling with a sample of 150 respondents. To test financial literacy, financial technology and social capital on financial inclusion using Partial Least Square (PLS) version 4.0. The results showed that financial literacy had a positive and significant effect on the financial inclusion of the people of Malang City, financial technology had a positive and significant effect on the financial inclusion of the people of Malang City, and social capital had a positive and significant effect on the financial inclusion of the people of Malang City .